Penerapan Bimbingan Tesis Berbasis Lesson Study terhadap Percepatan Penyelesaian Studi Mahasiswa dalam Menerapkan Model Problem Based Learning (PBL) - Suciati Suciati; Widha Sunarno; Sarwanto Sarwanto (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2017)
This study aims to determine the impact of the thesis guidance based lesson study (LS) to: 1) the acceleration of the student's accomplishment in Science Graduate Education Program UNS; and 2) the applicability of the implementation of problem based learning model. The method used in tne research was qualitative-descriptive. The population is all students of Semester 3rd in the Academic Year 2012/2013 at Postgraduate Science Education Program UNS. Samples were selected by purposive sampling as researchers’ guidance student (M) which included 4 students with the different background and occupation, namely: 1) M.1: undergraduate student of biology education and working as a teacher at SMP Negeri Surakarta with 10 years of teaching experience; 2) M.2: undergraduate student of biology education and working as a private high school teacher in Surakarta with 13 years of teaching experience; 3) M.3: undergraduate student of biology education is a fresh graduate and have not been taught; 4) M.4: undergraduate student of natural biology and working as a lecturer at the Academy of Private Nursing in Surakarta. Descriptive qualitative methods are used to seeing the impact of the use of the guidance of a thesis-based lesson study to accelerating student study completion. The data collection technique is a technique test and non-test using a questionnaire, observation and documentation. Furthermore, the data were analyzed descriptively qualitative and presented in tabular form. The results showed: 1) Guidance LS-based thesis has an effective effect on the acceleration of the completion of studies students at UNS Graduate Science Education Program at (22.2%); and 2) Guidance based thesis can reduce students’ difficulties in research so that the problem based learning model can be implemented fluently.